The Ka’ulayawaa festivals among the Wayùu. Exploring continuities and variations in forms, meanings and contexts through ethnographic sources - Alessandro Mancuso (Archivio Antropologico Mediterraneo)
In this paper I review and compare the main sources of information about the ka’ulayawaa festivals among the Wayùu, an Amerindian people inhabiting in the semiarid Guajira peninsula (Northern Colombia and Venezuela). For their peculiar mix of songs, dances, imitative plays and competitive games, inserted into a same festive framework, these festivals are particularly interesting to be studied as expressive metacommentaries (in the sense of Turner) of Wayùu social structures, cultural values and worldview. Nevertheless, they have not so far been the subject of a specific anthropological analysis, also because they ceased to be celebrated around the middle of the twentieth century, that is, before the beginning of the first professional ethnographic studies on this population. Any attempt of “reconstruction” of the form, meaning and context the ka’ulayawaa festivals, and of their place in the Wayùu “socio-cosmology” must take in account not only the convergences and the divergences in the descriptions present in the ethnographic documentation available, but also, and above all, the continuous processes of change that have affected the Wayùu, at least in the last five centuries and, with an accelerated pace, in the last hundred years, and to which their sociocultural forms dynamically adapted. Most historical and ethnographic sources argued that in the ka’ulayawaa festivals “theatrical” expressiveness prevailed over symbolic efficacy, and “playfulness” over “rituality”. However, there are very strong and complex relationships between this “festive” and “playful” character of the ka’ulayawaa festivals and a series of fundamental cosmological oppositions of the Wayùu worldview, as described in the ethnographic literature. From the analysis that I have conducted, it can be said that the imitative and competitive games performed during the ka’ulayawaa festivals conformed and, at the same time, “played”, with these socio-cosmological oppositions and the order that they imply. This argument is reinforced by the most recent historical and ethnographical sources on these festivals, which highlight how their good outcome was perceived and considered among many Wayùu people as a “serious matter” and a source of concern and care on the part of all participants, especially the organizers, to the point of requiring prior intervention and approval of superhuman entities. It is therefore appropriate to take in account the coexistence of these traits in the ka’ulayawaa festivals in view of their possible analysis from the point of view of current theoretical reflections in anthropology on the relationship between rituality, playfulness and cosmology.